PELATIHAN MEMBATIK ECOPRINT GUNA MENUMBUHKAN JIWA KEWIRAUSAHAAN PEREMPUAN BAGI IBU-IBU RUMAH TANGGA - Alifiulahtin Utaminingsih (P3M Politeknik Negeri Malang, 2020)
Entrepreneurship soul very important to growth to some one that have entrepreneurshipspirit. That is some that do creatively and inovatively. Entrepreneur have characteristic improveskills, confidence have good self determination or locus of control, risk taker and look at change ischance for warehousing. There are farming ecologies so many leafs and flowers from any plantsthat can be use to make ecoprint batik models. Entrepreneurship trainning based on this conditionso held trainning of batik ecoprint to increace skill for warehousing in Tegalweru village thateconomic creative based through ecoprint batik trainning to create new women entrepreneur inTegalweri village, Sub District Dau, Malang Distric